DOES THERMAL WEAKENING EXPLAIN BASIN INVERSION? - STOCHASTIC MODELLING OF THE THERMAL STRUCTURE BENEATH SEDIMENTARY BASINS - Hansen D.L.; Nielsen S.B. (My University, 2002)
The fact that basin inversion is possible long after the cessation of rifting indicates that at least some sedimentary basins are characterized by permanent relative weakness. This paper investigates whether the steady-state thermal structure in itself can provide the necessary pattern of rheological weakening to facilitate compressional inversion of a sedimentary basin. By Monte Carlo simulation of a two-dimensional thermal finite element model we find that, generally, the maximum Moho temperature, and therefore also the weakest upper mantle, is encountered beneath the flanks of the basin. The reason for this is heat refraction deviating away from the central parts of the sedimentary cover and into the adjacent basement highs. The weakest crust, however, is located in the center of the basin due to sediment thermal blanketing, lower confining pressure, and the presence of relatively weak sediments.
Keywords: BASIN INVERSION; THERMAL PROPERTIES; LITHOSPHERE; RHEOLOGY; MONTE CARLO ANALYSIS